2019
DOI: 10.3390/brainsci9100251
|View full text |Cite
|
Sign up to set email alerts
|

Does Video Gaming Have Impacts on the Brain: Evidence from a Systematic Review

Abstract: Video gaming, the experience of playing electronic games, has shown several benefits for human health. Recently, numerous video gaming studies showed beneficial effects on cognition and the brain. A systematic review of video gaming has been published. However, the previous systematic review has several differences to this systematic review. This systematic review evaluates the beneficial effects of video gaming on neuroplasticity specifically on intervention studies. Literature research was conducted from ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 86 publications
0
37
0
2
Order By: Relevance
“…Moreover, recent research showed that there are visible changes in MRI after the application of other cognitive and neuro-muscular training modalities, such as video-gaming, and immersive and non-immersive virtual reality as a recovery therapy. Thus, positive influences are found both at the level of neuro-motor evaluation methods and also at the imaging level [47,48].…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, recent research showed that there are visible changes in MRI after the application of other cognitive and neuro-muscular training modalities, such as video-gaming, and immersive and non-immersive virtual reality as a recovery therapy. Thus, positive influences are found both at the level of neuro-motor evaluation methods and also at the imaging level [47,48].…”
Section: Discussionmentioning
confidence: 98%
“…The divergences found in the present study can be explained by the fact that exergames are a relatively new technological achievement, making studies with different designs possible. However, it should be understood that promising opportunities exist with technologies that, for example, make people more active and promote motor skills, cognitive performance and mental health [ 46 , 47 ]. In terms of mental health, it is noteworthy that the present study found that exergames promote positive effects on self-esteem, self-efficacy, self-concept, help with interest and situational motivations, providing a sense of pleasure, psychological well-being and different learning experiences [ 30 , 41 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is noteworthy that there is a difference with people who play cooperatively in the form of competition, as those who are highly competitive report more positive moods and greater pleasure when placed in a competitive exergaming environment, while non-competitive participants report higher levels of pleasure, humor, self-efficacy, motivation, engagement and play for longer periods when placed in a non-competitive exergaming environment. Thus, video games can be beneficial to the brain, however, the benefits vary depending on the type of video game [ 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Video gaming is growing, not only as a gaming phenomenon but also as a field of study. Video gaming has been studied from a variety of different areas, such as rehabilitation of gait and balance problems (Ravenek et al, 2016), identifying gaming disorder (Kaptsis et al, 2016), neurological aspect of gaming (Palaus et al, 2017), how gaming affects the brain structure (Brilliant et al, 2019), potential associations between gaming and cognition (Röhlcke et al, 2018;Nuyens et al, 2019), and whether education can be gamified (Kim et al, 2018). Today, video gaming and e-sport are challenging more "traditional" sports in terms of the increasing amount of both recreation players and professional players.…”
Section: Introductionmentioning
confidence: 99%